MON-033 Androgen Increases the Accumulation of Advanced Glycation End Products in Granulosa Cells by Activating ER Stress in PCOS - Azhary, Jerilee Mariam Khong (J Endocr Soc, 2020)
Polycystic ovarian syndrome (PCOS) is associated with hyperandrogenism. Previously we found that androgen activated endoplasmic reticulum (ER) stress in granulosa cells of antral follicles in PCOS, contributing to ovarian fibrosis (1) and growth arrest of antral follicles (2). In addition, recent studies demonstrated the accumulation of advanced glycation end products (AGEs) in granulosa cells from PCOS patients, which contribute to its pathology. Based on these findings, we hypothesized that androgen upregulates the expression of the receptor for AGEs (RAGE) in granulosa cells of antral follicles by activating ER stress. This in turn, increases the accumulation of AGEs in these cells. In the present study, we found that testosterone induced the expression of RAGE and accumulation of AGE in cultured human granulosa-lutein cells (GLCs). These effects were inhibited with the treatment of tauroursodeoxycholic acid (TUDCA), a clinically available ER stress inhibitor agent. Knockdown of the transcription factor C/EBP homologous protein (CHOP), an unfolded protein response (UPR) factor activated by ER stress, inhibited the testosterone-induced RAGE expression and AGE accumulation. Pretreatment with flutamide, as well as knockdown of androgen receptor decreased the testosterone-induced RAGE expression. Expression of RAGE was increased in GLCs obtained from patients with PCOS. Concomitantly, the expression of RAGE and the accumulation of AGE was increased in granulosa cells of antral follicles from PCOS patients and dehydroepiandrosterone (DHEA)-induced PCOS mice. Administration of the RAGE inhibitor, FPS-ZM1 or TUDCA to PCOS mice, reduced the expression of RAGE and the accumulation of AGE in granulosa cells of antral follicles, accompanied by a reduction of atretic follicles and improvement in the estrous cycle. In summary, our findings indicate that hyperandrogenism in PCOS increases the expression of RAGE and accumulation of AGEs in the ovary by activating ER stress. The potential therapeutic benefit of targeting the AGE-RAGE system, either with a RAGE inhibitor or an ER stress inhibitor agents, may serve as a novel approach for the treatment of PCOS. (1) Takahashi et al. Sci Rep. 2017;7(1):10824. (2) Azhary et al. Endocrinol. 2019;160(1):119–132